Abdul Muluk Improvisation Techniques in the Warung Kajang Lako Program on TVRI Jambi - Irianto, Ikhsan Satria; Gunawan, Indra; Handayani, Lusi; Gustyawan, Tofan (Mudra Jurnal Seni Budaya, 2024)
One of the characteristics of traditional Indonesian theater, including Abdul Muluk Jambi, is that the performances rely on the improvisational abilities of the actors. Therefore, improvisation techniques are an essential element in traditional Indonesian theater acting, especially the Abdul Muluk Jambi theater. One of the theater groups that is intense in developing improvisation techniques based on Abdul Muluk's improvisations is Sanggar Pancarona Jambi. This research was conducted to find patterns of improvisational acting techniques in the Abdul Muluk performance by Sanggar Pancarona Jambi. The material object of this research is the performance of Abdul Muluk by Sanggar Pancarona which was broadcast on TVRI Jambi in the Warung Kajang Lako program. This event featured Abdul Muluk's appearance with a shortened duration. The selection of this object was based on the characteristics of the Abdul Muluk performance by Sanggar Pancarona which prioritizes the power of actor improvisation. To find patterns in Abdul Muluk's improvisation techniques, the research method used was a qualitative method with stages, observation, interviews and data analysis. The results achieved from this research are that Sanggar Pancarona Jambi uses improvisation techniques adopted from the Abdul Muluk Jambi theater. Abdul Muluk's improvisation technique which was applied at the Warung Kajang Lako TVRI Jambi event consisted of: Improvisation Rules, Building Agreement, Creating and Saying Topics, Creating Collective Imagination, Division of Tasks, Setting Timings, Starting from Introductions and Interacting with the Audience. The supporting element for Abdul Muluk's improvisation is music that is improvised in response to the actor's improvisation.